Figurative representations and their possibilities to understand the boundaries between Judaism and Christianity in Late Antiquity - Siqueira, Silvia M. A. (Romanitas - Revista de Estudos Grecolatinos, 2013)
The historical and religious analysis of the figurative representations in different religious contexts – the Jews and the Christian ones – allows us to deepen the reflections about the use of art as a conventional, symbolic and easy-to-understand language. However, our study establishes the differences among all these uses in a subtle way, not forgetting the use of the iconographic heritage to proselytize as a characteristic of Late Antiquity, as we intend to show in this article.